2012
DOI: 10.1371/journal.pone.0041086
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of N-Acetyl-Cysteine and Acetyl-L-Carnitine after Spinal Cord Injury in Adult Rats

Abstract: Following the initial acute stage of spinal cord injury, a cascade of cellular and inflammatory responses will lead to progressive secondary damage of the nerve tissue surrounding the primary injury site. The degeneration is manifested by loss of neurons and glial cells, demyelination and cyst formation. Injury to the mammalian spinal cord results in nearly complete failure of the severed axons to regenerate. We have previously demonstrated that the antioxidants N-acetyl-cysteine (NAC) and acetyl-L-carnitine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 79 publications
4
51
0
Order By: Relevance
“…They showed that both substances restored the density of dendritic branches and axons in the ventral horn of hemisected rat spinal cords. 22 However, Kaynar et al reported that a single dose of NAC administered intraperitoneally was ineffective after experimental spinal cord injury with an aneurysm clip in rats. 23 Naziroglu et al examined the effects of NAC and selenium on apoptosis and oxidative stress in the hippocampus of rats following brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that both substances restored the density of dendritic branches and axons in the ventral horn of hemisected rat spinal cords. 22 However, Kaynar et al reported that a single dose of NAC administered intraperitoneally was ineffective after experimental spinal cord injury with an aneurysm clip in rats. 23 Naziroglu et al examined the effects of NAC and selenium on apoptosis and oxidative stress in the hippocampus of rats following brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…[16,17] A variety of known antioxidants and anti-inflammatory agents have shown protective effects on traumatic SCI in experimental models and clinical trials. [18][19][20][21][22][23][24] Toklu et al [18] have found that alpha-lipoic acid reduces oxidative stress on traumatic SCI. Sahin et al [19] have shown significant protective effects of curcumin on traumatic spinal cord tissues against oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Sahin et al [19] have shown significant protective effects of curcumin on traumatic spinal cord tissues against oxidative damage. Karalija et al [20] have demonstrated better pathological findings by Nacetyl-cysteine and acetyl-L-carnitine in the early treatment of traumatic SCI by using quantitative immunohistochemistry and western blotting for neuronal and glial cell markers, and indicated a therapeutic potential for NAC and ALC in the early treatment of traumatic SCI. Cemil B et al [21] have put forward better pathological findings by aged garlic extract in the traumatic SCI against oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…ALC also increases the production of glutathione (GSH), giving it a bipartite effect and further increasing its therapeutic appeal (Pettegrew et al, 2000;Karalija et al, 2012). ALC is shown to have beneficial effects for a number of neurodegenerative diseases, including Parkinson disease, Alzheimer disease, and multiple sclerosis (Puca et al, 1990;Pettegrew et al, 2000;Tomassini et al, 2004).…”
Section: Mitochondrial-based Treatmentmentioning
confidence: 99%